1997
DOI: 10.1007/s004330050079
|View full text |Cite
|
Sign up to set email alerts
|

IV Perflubron emulsion versus autologous transfusion in severe normovolemic anemia: effects on left ventricular perfusion and function

Abstract: Intact cardiac compensatory mechanisms are necessary to maintain adequate tissue oxygenation during acute normovolemic hemodilution (ANH). Left ventricular (LV) perfusion, oxygenation and function were analyzed in an experimental whole-body model of profound ANH (Hct 9%) and effectiveness of a perfluorocarbon-based oxygen carrier in maintaining myocardial oxygenation and function was evaluated. A total of 22 anesthetized dogs were hemodiluted to Hct 20% followed by a simulated, controlled blood-loss phase in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 42 publications
1
18
0
5
Order By: Relevance
“…Fluorocrit was assessed in the same capillaries used for Hct measurements by centrifugation (Readacrit Centrifuge, Clay Adams) and is given as a percentage, representing the length of PCF emulsion (indicated by the white color) in the centrifuged capillary tube relative to the entire length of the centrifuged whole blood (consisting of subsequent layers of plasma, cells, and PCF emulsion) (7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorocrit was assessed in the same capillaries used for Hct measurements by centrifugation (Readacrit Centrifuge, Clay Adams) and is given as a percentage, representing the length of PCF emulsion (indicated by the white color) in the centrifuged capillary tube relative to the entire length of the centrifuged whole blood (consisting of subsequent layers of plasma, cells, and PCF emulsion) (7).…”
Section: Methodsmentioning
confidence: 99%
“…The low oxygen-carrying capacity of fluorocarbons in normoxic tissue can be augmented by exposing the organism to normobaric 100% oxygen, an approach taken in all attempts to produce an oxygen-carrying blood substitute with this material (7,9). Fluorocarbons to be used as blood substitutes would presumably be used to remedy blood losses, decreased oxygencarrying capacity, and anemia in conditions of anemic hyperoxia.…”
mentioning
confidence: 99%
“…In addition, Habler at al. found that mixed-venous O2 partial pressure was higher in perflubron emulsion treated animals after hemodilution to a Hb of 7 g/dL than in control animals (18,19) and also left ventricular contractility was improved after perflubron emulsion administration at a Hb level of 3 g/dl (20). This might be explained by an augmented O2 delivery through very narrow capillaries where perflubron emulsion particles (<0.2 µm) but less so the relatively large red blood cell (7-8 µm) may penetrate and thereby increase local tissue oxygenation including the myocardium (13).…”
Section: Introductionmentioning
confidence: 99%
“…In patients mobilised with G-CSF (CE 7.36%; 0.8-29.7) the contamination was greater than in unmobilised donors (0.83%; 0.5-6.8; Mann-Whitney-U-Test CE p=0.011). The hct decreased from 32% (23-40) to 29% (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)) and the platelets from 194G/l (11-966) to 105G/l (6-594). The contamination with platelets was lower compared to our own historical group ( 290 apheresis with the Fenwal CS3000; CE 6.7% versus 22.1%).…”
Section: P207 Predepletion Of Thrombocytes Improves the Yield Of Thementioning
confidence: 99%
“…In dogs initially hemodiluted on room-air ventilation to Hb 7 g/dl, subsequent hyperoxic ventilation allowed for further hemodilution to the extreme value of Hb 3 g/dl without encountering significant changes in tissue oxygenation ( fig. 5) [19] and cardiac performance [21]. Moreover, in pigs ventilated with room-air and diluted until the occurrence of manifest tissue hypoxia (Hb 2.6 g/dl), subsequent ventilation with 100% oxygen was not only able to effectively reverse tissue hypoxia ( fig.…”
Section: Experimental Datamentioning
confidence: 99%